تأثیر تمرینات مشابھة للأداء باستخدام الأشرطة المطاطیة في تطویر قوة التصویب ودقتھ للاعبین الشباب بكرة الید - حسام محمد هيدان; انتصار جمعة مبارك (الرياضة المعاصرة)
The means of training assistance from the requirements that must be provided in the training process of being given yields positive physical and skill , and this means training elastics , which is one of the means training resistors modern , which have many benefits to help the player in the development of potential physical and skill alike , so it was used in the development of the power correction and accuracy of the handball players have given positive results and the size of a big impact on the strength of the correction through prolongation and failure to working muscles , but in accuracy was the size of the impact a little and this result is a natural fact that accuracy is directly related to the work of the central nervous system and the nature of internal signals and stimuli of Foreign Affairs and needs to develop it into a longer time period , and this evolution in the power and precision reflected positively on the development of the correction is generally born members of the research sample the fact that these two qualities are most important in the correction handball , the play if not available, has the power or precision , or both adequately can not achieve success in shooting on goal , then the use of elastics in exercises similar to the performance of the skill of the correction handball have had impact in the development of kinetic paths of skill and adjusted in line with the amount of force required and accuracy at the same time.